Inovasi Olahan Ikan Tongkol Menjadi Ikan Suwir Pedas : Solusi Makanan Ekonomis dan Bergizi Untuk Anak Kost dan Masyarakat di Kelurahan Pantai Amal - Nurul Hidayat; Dwi Rahmawati; Jesika Dela Maharani; Gustini Berianti; Katharina Sandra Lisya; Muhammad Rizaldi; Yashar Arifandya Ramadhan; Yenni Sukmawati; Yulia Viani Nogo Tukan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Tongkol fish is one of the abundant sources of animal protein and is easily found in coastal areas, including Pantai Amal Village. However, the utilization of tongkol fish by the community is still limited to traditional processing that is less varied. On the other hand, fellow students often face challenges in meeting daily nutritional needs due to economic limitations and instant consumption patterns that are low in nutrition. This study aims to develop innovations in processing tongkol fish into spicy shredded fish as an economical, nutritious, and practical food solution. The research methods include the production process, taste testing, and analysis of production and consumption costs. The results show that spicy shredded fish has a high protein content, a taste that consumers like, and a fairly long shelf life so that it is suitable as a daily food stock. In addition, this product is proven to be more economical than consuming fast food, so it is effective in helping students from out of town manage their expenses while meeting their nutritional needs. This innovation also has the potential to increase the added value of tongkol fish and support local food security in coastal areas.